Generation of strut-and-tie models in concrete structures by topology optimization based on moving morphable components. Issue 7 (3rd July 2021) - Qiao, Wenzheng; Chen, Guorong
Abstract : Explicit topology optimization based on moving morphable components (MMCs) is a novel and revolutionary topology optimization framework that may be exploited for the generation of strut-and-tie models (STMs) in concrete structures. The article deals with the generation of STMs by solving a compliance minimization problem subject to a volume constraint. The feasible STMs are generated by a set of components that can move, dilate, shrink, overlap and merge. A new extraction method is adopted to address the crucial problem that interprets the topology optimization results as the STM. Design examples of deep beams and corbels are presented to demonstrate the validity and effectiveness of the MMC-based topology optimization method as a rational and reliable design tool for concrete structures. Moreover, the high efficiency and the applicability of the proposed approach to the multiple load case are also investigated.